DEVELOPMENT OF AN AUTOMATED SYSTEM FOR DETERMINING THE "ID OF THE COMPETITIVE PROPOSAL" OF THE SPECIALTY (EDUCATIONAL PROGRAM) - LYTVYN, Oleg; MAKATORA, Dmytro; DZHIKIYA, Nellie (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of the implementation of automated systems and the definition of the "ID of the competitive proposal" of the specialty (educational program) depending on the selected criteria, namely: educational level; admission base; specialty; form of education; the deadline for submitting documents allows you to choose CP in two versions: "Dates depending on the CP" – the search by date is not performed and all available competitive proposals are displayed in accordance with other criteria and "At the moment " – a search for competitive proposals that are available at a moment is added to the search criteria, which makes it possible to determine the "ID of the tender proposal". A flowchart of the algorithm has been developed that implements the above-described actions of automated systems and the definition of the “ID of the competitive proposal". The system has an adaptive design, and can be downloaded to various mobile devices, which will allow you to have information at the fingertips. Also, the system has a short reaction time, reduces the load on the server (since after receiving information from the database, it is processed on the user's computer). The automated system for determining the "ID of the competitive proposal" was posted on the https://www.vstup.org/konkurs portal, and the link to it on the site https://iino.knuba.edu.ua/. The system was tested during the admission campaign 2022 in the separate structural section and "Institute of Innovative Education of Kyiv National University of Construction and Architecture", confirmed its performance, the number of users who used the system was 1298 people, which is equal to 92% of the total number of applications for admission.
Keywords: admission campaign; ID of the competitive proposal; automated system; institutions of professional pre-higher education; institution and higher education; algorithm